Hydraulic mining operation, vicinity of Nome, n.d. - Nowell, Frank H., 1864-1950 (1894)
Caption on image: 4462 On verso of image: No. 2 Glacier owned by Price Bros. and operated by Miocene Ditch Co., Nome To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number